Applying the classroom assessment scoring system in classrooms serving students with emotional and behavioural disorders. Issue 4 (2nd October 2018) - Cipriano, Christina; Barnes, Tia N.; Bertoli, Michelle C.; Rivers, Susan E.
ABSTRACT: Students with Emotional and Behavioural Disorders (EBD) have the poorest academic and social outcomes across the general and special education student populations, and are among the most likely to receive instruction in self-contained special education classrooms hallmarked by small teacher-student ratios, frequent transitions, extreme student behaviours, and the regular presence of multiple adults in the room. These characteristics differentiate the interactions between adults and students occurring in self-contained versus inclusive or general education settings. With the goal of improving outcomes for students with EBD in self-contained classrooms, this study used mixed-methods to examine the psychometric properties of the widely used Classroom Assessment Scoring System (CLASS). Results suggest limitations in the applicability of the CLASS for self-contained classrooms.